Co-existence of clonal expanded autologous and transplacental-acquired maternal T cells in recombination activating gene-deficient severe combined immunodeficiency. (24th April 2014) - Lev, A; Simon, A J; Ben-Ari, J; Takagi, D; Stauber, T; Trakhtenbrot, L; Rosenthal, E; Rechavi, G; Amariglio, N; Somech, R
Summary: It is commonly accepted that the presence of high amounts of maternal T cells excludes Omenn syndrome (OS) in severe combined immunodeficiency (SCID). We report a SCID patient with a novel mutation in the recombination activating gene (RAG)1 gene (4-BP DEL.1406 TTGC) who presented with immunodeficiency and OS. Several assays, including representatives of specific T cell receptors (TCR), Vβ families and TCR-γ rearrangements, were performed in order to understand more clearly the nature and origin of the patient's T cells. The patient had oligoclonal T cells which, based on the patient–mother human leucocyte antigen (HLA)-B50 mismatch, were either autologous or of maternal origin. These cell populations were different in their numbers of regulatory T cells (Treg ) and the diversity of TCR repertoires. This is the first description of the co-existence of large amounts of clonal expanded autologous and transplacental-acquired maternal T cells in RAG1-deficient SCID.